2013
DOI: 10.4161/cc.24550
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptors induce FOXO1-dependent senescence in ovarian cancer cells

Abstract: Loss of nuclear progesterone receptors (PR) and low circulating progesterone levels are associated with increased ovarian cancer (OC) risk. However, PR are abundantly expressed in a significant percentage of serous and endometrioid ovarian tumors; patients with PR+ tumors typically experience longer progression-free survival relative to those with PR-null tumors. The molecular mechanisms of these protective effects are poorly understood. To study PR action in OC in the absence of added estrogen (i.e., needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 91 publications
(116 reference statements)
6
88
0
Order By: Relevance
“…Its risk has been reported not to be affected by oral contraceptives [16,17] but associations with HT use are inconsistent [7,17,18]. Progesterone receptor (PR) expression is lower in mucinous carcinomas than in other ovarian cancer subtypes [19] which may explain its resistance against the protective effect of oral contraceptives. Our finding of lower risk of both mucinous borderline ovarian tumors and mucinous carcinomas in the LNG-IUS users could be mediated by other mechanisms than direct progestin effect of LNG-IUS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its risk has been reported not to be affected by oral contraceptives [16,17] but associations with HT use are inconsistent [7,17,18]. Progesterone receptor (PR) expression is lower in mucinous carcinomas than in other ovarian cancer subtypes [19] which may explain its resistance against the protective effect of oral contraceptives. Our finding of lower risk of both mucinous borderline ovarian tumors and mucinous carcinomas in the LNG-IUS users could be mediated by other mechanisms than direct progestin effect of LNG-IUS.…”
Section: Discussionmentioning
confidence: 99%
“…High grade serous tumors cause the majority of deaths due to ovarian cancer [25]. Low grade serous ovarian carcinoma is a more indolent type originating from serous borderline tumors and does express high levels of PR [19,22,25]. In this study, serous carcinomas were analyzed as one group because data of tumor grades were not available.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] We tested 0.1 mM and 1 mM, and found AS1842856 severely suppressed adipogenesis at both concentrations, thus choosing to use 0.1 mM for the treatments if not specified elsewhere. AS1842856 or the vehicle 0.1% DMSO as a treatment control was supplemented through the whole procedure of BMI!DMI!DMII!BMII (Fig.…”
Section: As1842856 Treatmentsmentioning
confidence: 99%
“…23 It can potently inhibit the DNA binding of FoxO1 and its transactivation. [23][24][25] In hepatic cells, AS1842856 inhibits glucose production by suppressing G6P and PEPCK mRNA levels, and administration of AS1842856 to diabetic db/db mice significantly reduces fasting blood glucose. 23 However, the effect of AS1842856 on adipogenesis has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our results indicated that RC-6 can induce senescence characteristics in NT2 cells. Previous studies demonstrated that p27 protein increase was also found in senescence cells (49,68,69). However, p27 protein levels were not increased significantly in RC-6-treated NT2 cells.…”
Section: Discussionmentioning
confidence: 86%